Lutein/zeaxanthin isomers regulate neurotrophic factors and synaptic plasticity in trained rats - Orhan, Cemal; Erten, Fusun; Er, Besir; Tuzcu, Mehmet; SahIn, Nurhan; KurSun, Oznur Ece durmaz; SahIn, Kazim (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: This study was conducted to elucidate the effects of lutein/zeaxanthin isomers (L/Zi) on lipid metabolism, oxidative stress, NF-Kappa B/Nrf2 pathways, and synaptic plasticity proteins in trained rats. Materials and methods: Wistar rats were distributed into four groups: 1) control, 2) L/Zi: rats received L/Zi at the dose of 100 mg/kg by oral gavage, 3) exercise, 4) exercise+L/Zi: rats exercised and received L/Zi (100 mg/kg) by oral gavage. The duration of the study was eight weeks. Results: Exercise combined with L/Zi reduced lipid peroxidation and improved antioxidant enzyme activities of muscle and cerebral cortex in rats (p < 0.001). In the Exercise + L/Zi group, muscle and cerebral cortex Nrf2 and HO-1 levels increased, while NF-Kappa B levels decreased (p <0.001). Also, L/Zi improved BDNF, synapsin I, SYP, and GAP-43 levels of the cerebral cortex of trained rats (p < 0.001). The highest levels of BDNF, synapsin SYP, and GAP-43 in the cerebral cortex were determined in the Exercise+L/Zi group. Conclusion: These results suggested that exercise combined with L/Zi supplementation might be effective to reduce neurodegeneration via improving neurotrophic factors and synaptic proteins, and oxidative capacity in the cerebral cortex.
Keywords: Lutein; zeaxanthin; exercise; oxidative stress; synaptic proteins